Experimental investigation on the Reynolds dependence of the performance of branched heat exchangers working with organic fluids. (September 2019) - Capata, R.; Gagliardi, L.
Highlights: Branched exchangers . Three different branched exchangers were studied and designed. The heat exchangers is characterized by a specific requirement. The first by keeping the fluid efflux speed constant, the second by keeping the fluid Re number constant and the third according to constructal. Experimental tests . The branched exchangers were evaluated. The attention focused on the heat transfer and pressure losses. A proper test bench has been realized. All instruments data are considered and provided. Different fluids were used in tests. Fluids . In the first phase different fluids were studied such as water, oil, high density, and glycol. In the second phase an organic fluid is used. The organic fluid circuit is vacuum made. All tests assessed the thermal efficiency and pressure losses. Results . In addition to the results of the tests Nusselt, Prandtl and Reynolds dimensionless numbers were calculated. This has allowed to define the phenomena that regulate the thermal exchange. Comparative evaluation . Once all data have been available, the optimal exchanger configuration has been identified. Future developments concern the achievement of scale 1:5 exchangers and test consequential campaign. Abstract: The aim of this work is to continue the experimental evaluation of three different compact branched heat exchangers. To complete the previous study, additional experimental tests were carried out, using a commercial automotive refrigerant (Glycol) at different concentrations (50%, 100%). Finally, in order to have a deeper knowledge of this phenomenon and to identify the parameters regulating the heat transfer, an organic fluid has also been used and tested. The use of such a fluid has required a re-elaboration and design of the test bench. In fact, a vacuum circuit has been realized to properly use the organic fluid. As a result, the equipment used has been changed and inserting more sophisticated sensors. Finally, once all the tests have been completed, the various dimensionless parameters, characterizing the heat exchange, have been calculated and a comparative evaluation has been carried out, to determine and propose the optimal configuration of the branched heat exchanger.